Honeycomb-like biomimetic scaffold by functionalized antibacterial hydrogel and biodegradable porous Mg alloy for osteochondral regeneration - Zhang, Yongqiang; Dong, Qiangsheng; Zhao, Xiao; Sun, Yuzhi; Lin, Xin; Zhang, Xin; Wang, Tianming; Yang, Tianxiao; Jiang, Xiao; Li, Jiaxiang; Cao, Zhicheng; Cai, Tingwen; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Osteochondral repair is a significant challenge due to its unique pathological mechanisms and complex repair processes, especially in bacterial tissue conditions caused by open injury, infection and surgical contamination. The work introduced a biomimetic honeycomb-like scaffold (Zn-AlgMA@Mg) for osteochondral repair, composed of a dicalcium phosphate dihydrate (DCPD) coated porous magnesium scaffold (DCPD Mg) embedded within a dual crosslinked sodium alginate hydrogel (Zn-AlgMA), which synergistically exert antibacterial and osteochondral integrated repair properties. The DCPD Mg displayed a uniform porous structure and superior mechanical properties, and the Zn-AlgMA exhibited consistent microstructural features and enhanced hydrophilicity. The Zn-AlgMA@Mg scaffold provided controlled release of magnesium and zinc ions for cell proliferation and vitality, exhibiting significant osteogenic and chondrogenic properties as well as antibacterial efficacy in vitro. Proteomic analysis revealed the mechanism of osteochondral integrated repair from this scaffold. Micro-CT evaluation from three-dimensional reconstruction, quantitative analysis, and histology (including hematoxylin-eosin, Safranin-O, and Masson's trichrome staining) demonstrated that osteochondral integration was successful in the rabbit full-thickness osteochondral defect model. Therefore, this biomimetic honeycomb-like scaffold (Zn-AlgMA@Mg) provided a promising biomaterial for achieving integrated osteochondral regeneration.